Thermally conductive silicone adhesive composition and thermally conductive composite

The thermal conductivity silicone adhesive composition addresses adhesive strength and insulation issues in electronic devices by using specific organopolysiloxanes and fillers, ensuring efficient heat dissipation and strong fixation without high-pressure curing, enhancing device miniaturization and manufacturing efficiency.

JP7624377B2Active Publication Date: 2025-01-30SHIN ETSU CHEMICAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021187776
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-18
Publication Date
2025-01-30
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

Conventional thermal conductivity adhesives and tapes used in electronic devices suffer from poor adhesive strength, workability, and insulation issues, hindering efficient heat dissipation and device miniaturization due to the need for multiple parts and processes, and high-pressure curing methods.

Method used

A thermal conductivity silicone adhesive composition comprising specific organopolysiloxanes, thermal conductive fillers, and organic peroxides, which provides good adhesive strength and insulation without high-pressure curing, allowing for easy application and strong fixation between heat-generating elements and heat dissipation members.

Benefits of technology

The composition achieves effective heat conduction and strong adhesion between components, enabling efficient heat dissipation and reliable fixation without the need for high-pressure curing, thus supporting device miniaturization and improved manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624377000001
    Figure 0007624377000001
  • Figure 0007624377000002
    Figure 0007624377000002
  • Figure 0007624377000003
    Figure 0007624377000003
Patent Text Reader

Abstract

To provide a heat-conductive silicone adhesive composition which is excellent in handleability and with which sufficient adhesive strength can be obtained, and to provide a composite which is excellent in strength and insulation property.SOLUTION: A heat-conductive silicone adhesive composition contains the following components (a)-(e): (a) 100 pts.mass of a straight chain or branched organopolysiloxane; (b) 1,500-7,500 pts.mass of a heat-conductive filler; (c) 150-600 pts.mass of a three-dimensional netlike organopolysiloxane resin including a component (c-1), a three-dimensional netlike organopolysiloxane resin having an amount of alkenyl groups in a molecule of 0.05-0.15 mol / 100 g, and a component (c-2), a three-dimensional netlike organopolysiloxane resin; (d) 1-25 pts.mass of an organohydrogenpolysiloxane having two or more hydrosilyl groups in a molecule; and (e) 5-50 pts.mass of an organic peroxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive silicone adhesive composition and a thermally conductive composite. [Background technology]

[0002] Semiconductors such as transistors used in electronic devices and LED elements that serve as light sources for lighting, etc., have begun to generate large amounts of heat as they become more powerful, faster, smaller, and more integrated. The temperature rise in the device caused by this heat can lead to malfunctions or destruction of the device. For this reason, many heat dissipation methods and heat dissipation materials used for them have been proposed to suppress the temperature rise of semiconductors during operation.

[0003] Conventionally, in electronic devices, heat generated from semiconductors is transferred to cooling members such as heat sinks and housings made of metal plates with high thermal conductivity through thermally conductive materials, and dissipated to the outside. Thermally conductive sheets with insulating properties are often used as thermally conductive materials. Screws and clips are used to fasten the cooling members and semiconductors. The thermally conductive sheets between them are also fastened by pressure from the screws and clips. However, fastening methods using screws and clips require many parts and processes, which makes manufacturing efficiency very poor. In addition, parts such as screws and clips prevent the electronic devices themselves from being made smaller and thinner, which is very disadvantageous in terms of product design.

[0004] Therefore, a method of fixing the housing and the semiconductor element by imparting adhesiveness to the thermally conductive sheet interposed between the cooling member and the semiconductor is considered. Specifically, there is a method of applying an adhesive to both sides of a thermally conductive sheet to make a thermally conductive sheet with adhesive. However, since the adhesive itself does not have thermal conductivity, the thermally conductive sheet with adhesive has a significantly poor heat transfer. Therefore, for example, thermally conductive adhesive tapes using a thermally conductive filler as an adhesive are known, as described in Patent Documents 1, 2, and 3. In addition, Patent Document 4 discloses a thermally conductive silicone adhesive tape using silicone as a polymer due to its heat resistance, cold resistance, and durability.

[0005] However, conventional adhesive tapes have poor adhesive strength compared to general adhesive materials, and there were issues with making them screwless. Furthermore, in the case of single-layer adhesive tapes, there was also room for improvement in terms of workability, insulation, and strength. On the other hand, adhesive tapes are characterized by the fact that they can obtain better adhesive strength than adhesive tapes by applying heat and pressure. However, in general, in order to obtain sufficient adhesive strength, a process of heating under high pressure is required, so in some cases they could not be used for heat dissipation components that are sensitive to pressure.

[0006] On the other hand, some types of heat-curing adhesives that are not in sheet form have high adhesion to heat dissipation components, and can provide high adhesive strength and heat dissipation performance. However, there are issues such as the work process during application being complicated, inferior workability and reworkability compared to adhesive (bonding) sheets, and the risk of voids being mixed in. Furthermore, with addition-curing adhesives, refrigerated storage is often recommended to prevent deterioration of adhesive strength over time, and there is also room for improvement in terms of increasing process management by users. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-34652 A [Patent Document 2] JP 2014-62220 A [Patent Document 3] JP 2002-121529 A [Patent Document 4] JP 2008-260798 A Summary of the Invention [Problem to be solved by the invention]

[0008] Accordingly, an object of the present invention is to provide a thermally conductive silicone adhesive composition that has good handleability and can obtain sufficient adhesive strength. Another object is to provide a composite excellent in strength and insulation properties.

Means for Solving the Problems

[0009] As a result of intensive studies to achieve the above object, the inventors of the present invention have found that by specifying the composition of the silicone resin and the blending amount of the thermally conductive filler contained in the thermally conductive silicone adhesive composition, good handleability can be achieved, and an adhesive layer having good adhesive strength with a heat dissipation member can be provided, thus arriving at the present invention.

[0010] That is, the present invention provides a thermally conductive silicone adhesive composition containing the following components (a) to (e). (a) Linear or branched organopolysiloxane: 100 parts by mass (b) Thermally conductive filler: 1,500 to 7,500 parts by mass (c) Three-dimensional network organopolysiloxane resin containing the following components (c-1) and (c-2): 150 to 600 parts by mass (c-1): The following general formula (1) [Chemical formula] (In the formula, R 1 are independently selected from a group consisting of an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, R 2 is an alkenyl group having 2 to 8 carbon atoms, a1, b1, c1, d1 and e1 are numbers satisfying 0 < a1 ≤ 100, numbers satisfying 0 < b1 ≤ 100, numbers satisfying 0 ≤ c1 ≤ 100, numbers satisfying 0 ≤ d1 ≤ 100, numbers satisfying 0 ≤ e1 ≤ 100, and 0 < d1 + e1, and satisfy the range of 0.5 ≤ a1 / (d1 + e1) ≤ 2) represented by, and the amount of alkenyl groups in the molecule is 0.05 to 0.15 mol / 100 g of a three-dimensional network organopolysiloxane resin (c-2): The following general formula (2) [Chemical formula] (In the formula, R 1 is independently selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, and a2, c2, d2, and e2 are numbers satisfying 0 < a2 ≤ 100, numbers satisfying 0 ≤ c2 ≤ 100, numbers satisfying 0 ≤ d2 ≤ 100, and numbers satisfying 0 < e2 ≤ 100, respectively, and satisfy the range of 0.7 ≤ a2 / e2 ≤ 2.5) Three-dimensional network organopolysiloxane resin represented by (d) Organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule: 1 to 25 parts by mass, and (e) Organic peroxide: 5 to 50 parts by mass.

[0011] The present invention also provides the above thermally conductive silicone adhesive composition, wherein the thermally conductive silicone adhesive composition further contains (f) one or more selected from the following components (f-1) and (f-2) in an amount of 1 to 50 parts by mass. (f-1) An alkoxysilane compound represented by the following general formula (3) [Chemical formula] (In the formula, R 3 is independently an alkyl group having 6 to 15 carbon atoms, R 4 is independently an alkyl group having 1 to 5 carbon atoms, R 5 is independently an alkyl group having 1 to 6 carbon atoms, m is an integer of 1 to 3, n is an integer of 0 to 2, provided that m + n is an integer of 1 to 3) (f-2) Dimethylpolysiloxane represented by the following general formula (4) [Chemical formula] (In the formula, R 5 is independently an alkyl group having 1 to 6 carbon atoms, and p is an integer of 5 to 100). The present invention further provides a thermally conductive composite obtained by forming the thermally conductive silicone adhesive composition containing the above components (a) to (e) into a sheet and laminating it with a reinforcing layer. Effect of the Invention

[0012] The heat conductive silicone adhesive composition of the present invention is easy to handle and can be easily mounted on a heat dissipating member. In addition, the heat conductive silicone adhesive composition provides favorable thermal conductivity between a heat generating element and a heat dissipating member, and exhibits good adhesive strength, enabling strong fixation between the members. In addition, when thermocompression bonding (bonding) with a heat dissipating member, a curing process accompanied by high pressure is not required, and the composition is cured by leaving it at high temperature for a certain period of time, and sufficient adhesive strength is obtained, so that the composition can be applied to the bonding of a wide range of heat dissipating members.

[0013] Furthermore, by laminating a thermally conductive adhesive layer made of a thermally conductive silicone adhesive composition on both sides of a reinforcing layer to form a thermally conductive composite, it is possible to reinforce the strength and insulating properties. Therefore, the thermally conductive silicone adhesive composition of the present invention is extremely effective as a thermally conductive member that is interposed between a heat-generating element and a heat-dissipating member to transfer heat generated by the heat-generating element to the heat-dissipating member and to secure the elements in place. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in detail. The thermally conductive silicone adhesive composition of the present invention is characterized by containing the above components (a) to (e), each of which will be described in detail below.

[0015] (a) Organopolysiloxane Component (a) is a linear or branched organopolysiloxane, and is preferably an organopolysiloxane represented by the following average composition formula (5). [ka] (In the formula, R is, independently of each other, a monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is a positive number of 1.98 to 2.02.)

[0016] In the above formula, R are each independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably a monovalent hydrocarbon group having 1 to 8 carbon atoms. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, and butyl groups, cycloalkyl groups such as cyclohexyl groups, alkenyl groups such as vinyl, allyl, butenyl, and hexenyl groups, and aryl groups such as phenyl and tolyl groups. Methyl, vinyl, and phenyl groups are preferred.

[0017] The organopolysiloxane (a) may or may not have an alkenyl group in one molecule. When the organopolysiloxane (a) does not have an alkenyl group, preferably, 50 mol % or more of the total number of the substituents R in the organopolysiloxane represented by the above formula (5) are methyl groups, more preferably, 80 mol % or more are methyl groups, and particularly preferably, all of the substituents R are methyl groups.

[0018] When the organopolysiloxane (a) has alkenyl groups, it has 2 or more alkenyl groups in the molecule, more preferably 2 to 20 alkenyl groups, and even more preferably 2 to 10 alkenyl groups. The substituents R other than alkenyl groups are preferably 50 mol % or more, and particularly preferably 80 mol % or more of methyl groups, based on the total number of the substituents R in the organopolysiloxane of the above formula (5).

[0019] The organopolysiloxane (a) is preferably linear, but may have some branching within a range that does not impair the rubber strength as a thermally conductive adhesive, and may be a mixture of two or more organopolysiloxanes with different molecular structures and polymerization degrees. The organopolysiloxane (a) preferably has an average degree of polymerization of 100 to 20,000, particularly 200 to 10,000. The average degree of polymerization can be determined as a number-average degree of polymerization in terms of polystyrene by gel permeation chromatography (GPC). The organopolysiloxane (a) is preferably a diorganopolysiloxane raw rubber having an average degree of polymerization of 3,000 to 20,000, preferably 5,000 to 15,000, and a diorganopolysiloxane oil having an average degree of polymerization of 100 to 1,500, preferably 300 to 1,000. The latter is preferably a diorganopolysiloxane oil having alkenyl groups at both ends.

[0020] (b) Thermally conductive filler (b) The thermally conductive filler may be a known filler contained in a thermally conductive silicone composition, but is preferably at least one selected from the group consisting of metals, metal oxides, and metal nitrides. Known thermally conductive fillers may be used, such as non-magnetic metals such as copper and aluminum, metal oxides such as alumina, silica, magnesia, red iron oxide, beryllia, titania, and zirconia, metal nitrides such as aluminum nitride, silicon nitride, and boron nitride, artificial diamond, and silicon carbide. The thermally conductive filler has an average particle size of 0.1 to 50 μm, preferably 0.5 to 45 μm, preferably 0.8 to 40 μm, and more preferably 1 to 30 μm. The thermally conductive filler may be used alone or in combination with a plurality of types. In addition, two or more types of particles having different average particle sizes may be used. In the present invention, the average particle size is a volume average particle size, and is a value measured by a Microtrack particle size distribution measuring device MT3300EX (Nikkiso Co., Ltd.).

[0021] The above-mentioned thermal conductive filler may be subjected to various known surface treatments as long as the effects of the present invention such as thermal conductivity are not significantly impaired. For example, coupling agent treatments such as silane-based and titanate-based treatments and plasma treatment can be mentioned.

[0022] The compounding amount of the thermal conductive filler is characterized in that it is 1,500 to 7,500 parts by mass with respect to 100 parts by mass of the component (a), preferably 2,000 to 6,500 parts by mass. If the compounding amount of the thermal conductive filler is too large, the tape becomes brittle and the workability deteriorates. On the other hand, if the compounding amount is too small, the desired thermal conductivity cannot be obtained.

[0023] (c) Three-dimensional network organopolysiloxane resin (c) The three-dimensional network silicone resin, which is a component, functions to impart cohesive force to the tape and workability, and to provide good adhesive strength in the adhesive layer after curing. The component (c) is a three-dimensional network organopolysiloxane resin containing the following component (c-1) and component (c-2). (c-1): The following general formula (1)

Chemical formula

Chemical formula

[0024] (c-1) Component (Component (c-1) is a three-dimensional network organopolysiloxane resin represented by the above general formula (1), in which the alkenyl group in the molecule is 0.05 to 0.15 mol / 100 g. It is characterized in that the alkenyl group in the molecule is 0.05 to 0.15 mol / 100 g, preferably 0.06 to 0.14 mol / 100 g, more preferably 0.07 to 0.12 mol / 100 g. If the alkenyl group in the molecule is less than 0.05 mol / 100 g, it is difficult to obtain sufficient adhesive strength, so it is not preferable. If it is more than 0.15 mol / 100 g, the tape becomes hard and brittle, and the workability deteriorates, so it is not preferable.)

[0025] In the above formula (1), R 1 are, independently of each other, groups selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms. For example, alkyl groups such as methyl group, ethyl group, propyl group, butyl group, pentyl group, hexyl group, cyclohexyl group, heptyl group; aryl groups such as phenyl group, tolyl group, xylyl group, naphthyl group; aralkyl groups such as benzyl group, phenethyl group, etc. are mentioned. In particular, a methyl group and a vinyl group are preferable.)

[0026] In the above formula (1), R 2 are, independently of each other, alkenyl groups having 2 to 8 carbon atoms. For example, vinyl group, allyl group, butenyl group, pentenyl group, hexenyl group, cyclohexenyl group, and heptenyl group, etc. are mentioned. In particular, a vinyl group is preferable.)

[0027] In the above formula, a1, b1, c1, d1, and e1 satisfy 0 < a1 ≤ 100, 0 < b1 ≤ 100, 0 ≤ c1 ≤ 100, 0 ≤ d1 ≤ 100, 0 ≤ e1 ≤ 100, 0 < d1 + e1, and are numbers satisfying the range of 0.5 ≤ a1 / (d1 + e1) ≤ 2. Preferably, 1 ≤ a1 ≤ 50, 1 ≤ b1 ≤ 50, 0 ≤ c1 ≤ 50, preferably 0 ≤ d1 ≤ 50, and 1 ≤ e1 ≤ 50. (c-1) is trifunctional R 1 SiO 3 / 2 units (T units) and at least one branched-chain siloxane unit selected from tetrafunctional SiO 4 / 2 units (Q units). R 1 3SiO 1 / 2 The number (a1) of units (M units) and the ratio (a1 / (d1 + e1)) of the total number of the number (d1) of R 1 SiO 3 / 2 units (T units) and the number (e1) of SiO 4 / 2 units (Q units) shall satisfy the range of 0.5 ≤ a1 / (d1 + e1) ≤ 2, preferably the range of 0.6 ≤ a1 / (d1 + e1) ≤ 1.8, and more preferably the range of 0.7 ≤ a1 / (d1 + e1) ≤ 1.5.

[0028] When the above ratio is less than 0.5, it becomes difficult to highly fill the thermally conductive filler as the (b) component, and the thermal conductivity of the tape decreases. Or when the above ratio exceeds 2, the cohesive force of the tape decreases and the workability decreases.

[0029] (c-2) Component (c-2) component is a three-dimensional network organopolysiloxane resin represented by the above general formula (2) and having no alkenyl group.

[0030] In the above formula (2), R 1is, independently of each other, a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms. For example, alkyl groups such as methyl group, ethyl group, propyl group, butyl group, pentyl group, hexyl group, cyclohexyl group, heptyl group; aryl groups such as phenyl group, tolyl group, xylyl group, naphthyl group; aralkyl groups such as benzyl group, phenethyl group, etc. may be mentioned. In particular, a methyl group and a vinyl group are preferable.

[0031] In the above formula (2), a2, c2, d2 and e2 are numbers satisfying 0 < a2 ≤ 100, 0 ≤ c2 ≤ 100, 0 ≤ d2 ≤ 100, and 0 < e2 ≤ 100, and satisfying the range of 0.7 ≤ a2 / e2 ≤ 2.5. Preferably, 1 ≤ a2 ≤ 50, 0 ≤ c2 ≤ 50, 0 ≤ d2 ≤ 50, and 1 ≤ e2 ≤ 50. R 1 3SiO 1 / 2 The number (a2) of units (M units) and SiO 4 / 2 The ratio (a2 / e2) of the number (e2) of units (Q units) satisfies the range of 0.7 ≤ a2 / e2 ≤ 2.5, preferably the range of 0.8 ≤ a2 / e2 ≤ 2.2, and more preferably the range of 0.9 ≤ a2 / e2 ≤ 2.

[0032] When the above (a2 / e2) ratio is less than the above lower limit value, it becomes difficult to highly fill the thermally conductive filler as the (b) component, and the thermal conductivity of the tape decreases. Alternatively, when the above (a2 / e2) ratio exceeds the above upper limit value, the cohesive force of the tape decreases and the desired adhesive strength cannot be obtained.

[0033] In addition, R 1 is most preferably all methyl groups for reasons such as cost, availability, chemical stability, environmental load, etc., unless special properties such as solvent resistance are required.

[0034] The three-dimensional network organopolysiloxane resin as the (c) component can be used as a toluene solution of 50 to 70% by mass in the case of a solid. The kinematic viscosity in that case is 10 to 500 mm 2 / s, preferably 100 to 250 mm2 The kinematic viscosity is a value at 25°C measured using a Cannon-Fenske viscometer described in JIS Z8803:2011.

[0035] The value of a1 / (d1+e1) in the above (c-1) component and the value of a2 / e2 in the above (c-2) component are 29 It can be determined from Si-NMR. 29 There are no particular limitations on the method for preparing a sample for Si-NMR, but for example, the measurement can be performed by dissolving 1 part by mass of organopolysiloxane resin in 3 parts by mass of deuterated chloroform.

[0036] The component (c) of the present invention is characterized by including a combination of the above-mentioned component (c-1) and component (c-2). The compounding ratio of the components (c-1) and (c-2) is preferably such that the amount of the component (c-1) is 10 to 60 mass% relative to the total amount of the components (c), and more preferably 15 to 50 mass%. When the ratio of the component (c-1) is within this range, the obtained cured product can have good adhesive strength. The compounding ratio of the component (c-2) may be such that the amount of the component (c-1) satisfies the above range, and is preferably 40 to 90 mass%, and more preferably 50 to 85 mass% relative to the total amount of the components (c).

[0037] The amount of component (c) in the composition is 150 to 600 parts by mass, preferably 200 to 550 parts by mass, and more preferably 250 to 500 parts by mass, per 100 parts by mass of component (a). If the amount of component (c) added is less than the lower limit, the thermally conductive adhesive layer cannot obtain the desired adhesive strength. If the amount exceeds the upper limit, the tape becomes brittle and has poor flexibility, making workability difficult.

[0038] Component (c) is a solid or viscous liquid at room temperature and can be used dissolved in a solvent. In that case, the amount added to the composition can be adjusted so that the resin content excluding the solvent content falls within the above range.

[0039] (d) Organohydrogenpolysiloxane having two or more hydrosilyl groups in one molecule Component (d) is an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms (i.e., hydrosilyl groups) in one molecule, and functions to exhibit good wettability with the adherend interface and increase adhesive strength. The organohydrogenpolysiloxane may be a known compound, but it is preferable that the organohydrogenpolysiloxane does not substantially contain hydroxyl groups bonded to silicon atoms (i.e., silanol groups) in the molecule. The organohydrogenpolysiloxane may be used alone or in combination of two or more types.

[0040] The organohydrogenpolysiloxane can be represented by the following average composition formula (6). [ka] In the above formula (6), R 6 are each independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms. However, they do not have an aliphatic unsaturated bond such as an alkenyl group. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl groups, aryl groups such as phenyl, tolyl, xylyl, and naphthyl groups, and aralkyl groups such as benzyl, phenylethyl, and phenylpropyl groups. Among them, an alkyl group or an aryl group is preferred, and a methyl group is more preferred. In addition, r is a positive number of 0.7 to 2.1, preferably a positive number of 1.0 to 2.0. s is a positive number of 0.001 to 1.0, preferably a positive number of 0.01 to 1.0. Furthermore, r+s is a number that satisfies the range of 0.8 to 3.0, and preferably a number that satisfies the range of 1.5 to 2.5.

[0041] The organohydrogenpolysiloxane has 2 to 200, preferably 3 to 100, and more preferably 4 to 50 hydrosilyl groups in one molecule. The hydrosilyl groups may be located at either the terminal or the middle of the molecular chain, or may be located at both. The molecular structure of the organohydrogenpolysiloxane may be any of a linear, cyclic, branched, and three-dimensional network structure. The number of silicon atoms (degree of polymerization) in one molecule is usually 2 to 300, preferably 3 to 150, and more preferably 4 to 100. The degree of polymerization can be determined, for example, as the number average degree of polymerization (number average molecular weight) in terms of polystyrene in GPC (gel permeation chromatography) analysis using toluene as a developing solvent.

[0042] Examples of the organohydrogenpolysiloxane include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane copolymer capped with trimethylsiloxy groups at both molecular chain ends, and dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane capped with trimethylsiloxy groups at both molecular chain ends. dimethylhydrogensiloxy group-blocked methylhydrogenpolysiloxane at both molecular ends, dimethylpolysiloxane at both molecular ends, dimethylsiloxane-methylhydrogensiloxane copolymer at both molecular ends, dimethylsiloxane-methylphenylsiloxane copolymer at both molecular ends, dimethylsiloxane-diphenylsiloxane copolymer at both molecular ends, methylphenylpolysiloxane at both molecular ends, and diphenylpolysiloxane at both molecular ends, in which some or all of the methyl groups have been replaced by other alkyl groups such as ethyl or propyl groups, and compounds of the formula: R 2 3SiO 1 / 2 (R in the formula 2 is a monovalent hydrocarbon group other than an alkenyl group, and the R 1 The siloxane unit represented by the formula: R 2 2HSiO 1 / 2 Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R 2 2HSiO 1 / 2Siloxane units represented by the formula: SiO 4 / 2 Organosiloxane copolymers consisting of siloxane units represented by the formula: R 2 HSiO 2 / 2 Siloxane units represented by the formula: R 2 SiO 3 / 2 Siloxane unit or formula: HSiO 3 / 2 Examples of the organosiloxane copolymer include those having siloxane units represented by the following formula: These organohydrogenpolysiloxanes may be used in combination of two or more kinds.

[0043] The amount of component (d) is 1 to 25 parts by mass, preferably 5 to 20 parts by mass, per 100 parts by mass of component (a). If the amount of component (d) is less than the lower limit, the wettability to the adherend decreases, and the adhesive strength decreases. If the amount of component (d) is more than the upper limit, the adhesive layer becomes fragile, and the adhesive strength decreases.

[0044] (e) Organic peroxide The (e) component is an organic peroxide that decomposes under certain conditions to generate free radicals, and functions to promote the curing of the thermally conductive adhesive layer at high temperatures and to increase the adhesive strength. The organic peroxide may be a conventionally known one, and is not particularly limited, and may be used alone or in appropriate combination of two or more. For example, peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane and 2,2-di(4,4-di-(t-butylperoxy)cyclohexyl)propane, hydroperoxides such as p-menthane hydroperoxide and diisopropylbenzene hydroperoxide, dialkyl peroxides such as dicumyl peroxide and t-butylcumyl peroxide, diacyl peroxides such as dibenzoyl peroxide and disuccinic acid peroxide, peroxyesters such as t-butyl peroxyacetate and t-butyl peroxybenzoate, and peroxydicarbonates such as diisopropyl peroxydicarbonate. In particular, the use of peroxyketals, hydroperoxides, dialkyl peroxides, and peroxyesters, which have relatively high decomposition temperatures, is preferred from the viewpoint of ease of handling and storage. These organic peroxides may be used after being diluted with any organic solvent, hydrocarbon, liquid paraffin, inert solid, or the like.

[0045] The amount of component (e) is 5 to 50 parts by mass, preferably 10 to 45 parts by mass, per 100 parts by mass of component (a). If the amount of component (e) is less than the lower limit, the thermally conductive adhesive layer will not be cured sufficiently when cured after being fixed to the heat dissipation member, resulting in a decrease in adhesive strength. If the amount of component (e) is more than the upper limit, the adhesive strength will decrease when cured due to the large effect of decomposition residues.

[0046] (f) Surface treatment agent The silicone composition preferably further contains (f) a surface treatment agent. The (f) component functions to uniformly disperse the (b) thermally conductive filler in the (a) organopolysiloxane matrix during the preparation of the composition. The (f) component is at least one selected from the group consisting of an alkoxysilane compound represented by the following (f-1) component and a dimethylpolysiloxane containing a trialkoxy group at one end of the molecular chain represented by the following (f-2). That is, the (f-1) component and the (f-2) component may be used either alone or in combination. (f-1) An alkoxysilane compound represented by the following general formula (3): [ka] (In the formula, R 3 are each independently an alkyl group having 6 to 15 carbon atoms, and R 4 are each independently an alkyl group having 1 to 5 carbon atoms, and R 5 are each independently an alkyl group having 1 to 6 carbon atoms, m is an integer of 1 to 3, and n is an integer of 0 to 2, with the proviso that m+n is an integer of 1 to 3. (f-2) Dimethylpolysiloxane represented by the following general formula (4): [ka] (In the formula, R 5 are each independently an alkyl group having 1 to 6 carbon atoms, and p is an integer of 5 to 100.

[0047] In the above general formula (3), R 3 Examples of the alkyl group represented by R include a hexyl group, an octyl group, a nonyl group, a decyl group, a dodecyl group, and a tetradecyl group. 3 When the number of carbon atoms in the alkyl group represented by the formula (I) is in the range of 6 to 15, the wettability of the above-mentioned component (b) is sufficiently improved, the handleability is good, and the composition has good properties.

[0048] R 4 is an alkyl group having 1 to 5 carbon atoms, preferably having 1 to 3 carbon atoms, and particularly preferably a methyl group.

[0049] R 5 is an alkyl group having 1 to 6 carbon atoms, and preferably an alkyl group having 1 to 4 carbon atoms. Examples include a methyl group, an ethyl group, a propyl group, and a butyl group. A methyl group is more preferred.

[0050] The amount of component (f) is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and even more preferably 10 to 35 parts by mass, per 100 parts by mass of component (a). If the amount of component (f) added is less than the lower limit, it is difficult to highly fill component (b) into component (a). If the amount exceeds the upper limit, the adhesive strength is significantly reduced when the component (f) is incorporated into a thermally conductive adhesive layer.

[0051] In addition to the above-mentioned components (a) through (f), pigments and dyes for coloring, flame retardants, and various other additives for improving functionality can also be added to the above thermally conductive silicone adhesive composition, provided the addition does not impair the object of the present invention.

[0052] The thermally conductive silicone adhesive composition is prepared by uniformly mixing the above-mentioned components (a) to (e), optional component (f), and other components. The mixing method may be a conventionally known method. Preferably, components (a), (b), and (c) and optional component (f) are mixed together, and then components (d) and (e) are mixed.

[0053] The thermally conductive silicone adhesive composition is applied to a substrate as described below in the form of a thin tape, molded, and dried to obtain the thermally conductive adhesive layer in the thermally conductive composite of the present invention. The drying conditions are 60 to 100°C for 5 to 20 minutes, preferably 70 to 90°C for 5 to 15 minutes. If the drying conditions are outside the above range, the thermal conductivity decreases due to residual solvent, or the curing reaction of the composition proceeds, making it difficult to adhere the thermally conductive adhesive layer after drying to the heat dissipation member. The thermally conductive adhesive layer of the present invention is an uncured thermally conductive silicone adhesive composition, and when mounted between the heat dissipation member and the heat generation member, it is subjected to a heat curing treatment to firmly bond the two.

[0054] The thickness of the thermally conductive adhesive layer of the present invention is preferably 50 to 300 μm, more preferably 75 to 250 μm. If the thickness of the adhesive layer is less than 50 μm, the tape is difficult to handle and the adhesive strength is reduced. On the other hand, if the thickness of the adhesive layer exceeds 300 μm, it is difficult to obtain the desired thermal conductivity. In addition, when coating and molding, a solvent such as toluene or xylene can be added to adjust the viscosity. The thermally conductive adhesive layer may be one layer or a laminate of two or more layers. In particular, when the adhesive layer is thick, for example, when the thickness of the adhesive layer exceeds 250 μm, if the adhesive composition is applied thickly in one go, the thickness of the adhesive layer is likely to be uneven, and problems such as the separator film described below breaking during coating and molding are likely to occur. Therefore, it is preferable to apply the adhesive composition thinly in multiple layers to form a laminate of two or more layers. In addition, when a laminate of two or more layers is formed, the thermally conductive silicone adhesive composition of each layer may be the same or different.

[0055] The thermally conductive adhesive layer of the present invention can have a substrate surface-treated with a release agent as a separator film. That is, both sides of the thermally conductive adhesive layer may be protected with a release-treated film. By laminating a separator film on the adhesive surface, handling such as transportation and cutting to a fixed length can be facilitated. In this case, it is also possible to adjust the peeling force of the separator film by changing the amount and type of release agent and the material of the film.

[0056] The separator film is preferably a polyethylene laminated paper or a PET film whose surface is subjected to a release treatment with a cured film of a fluorine-modified silicone having a fluorine substituent bonded to the main chain, such as a perfluoroalkyl group or a perfluoropolyether group. The perfluoropolyether group can be represented by the following formulas (7) to (9). [ka] (k is 1 to 5, and q is 3 to 10)

[0057] Examples of commercially available fluorine-modified silicones that can be used include X-70-201, X-70-258, and X-41-3035 manufactured by Shin-Etsu Chemical Co., Ltd. Methods for molding onto a substrate include coating a liquid material onto the substrate using a bar coater, knife coater, comma coater, spin coater, or the like, but are not limited to the methods described above.

[0058] The thermally conductive adhesive layer of the present invention, although in the form of a thin tape or sheet, can be easily arranged at a desired location and exhibits excellent thermal conductivity. In addition, by having the above-mentioned separator film, one separator film is peeled off and then attached to a heat-generating electronic component or a heat-dissipating component, and then the remaining separator film is peeled off and attached to a cooling component, etc., so that it can be interposed between the cooling component and the heat-generating electronic component or the heat-dissipating component.

[0059] Furthermore, by using a heating element to generate heat or by carrying out a heat treatment after mounting, good adhesion between the components can be achieved, enabling strong fixation. The heat treatment after mounting is carried out at 130°C to 190°C for 20 to 90 minutes, preferably at 150°C to 170°C for 30 to 60 minutes, and pressure application during heating is not particularly required.

[0060] Furthermore, the thermally conductive composite of the present invention is obtained by laminating a reinforcing layer, which will be described later, on the thermally conductive adhesive layer in order to reinforce the strength and insulating properties. The reinforcing layer in the present invention is preferably made of glass cloth or synthetic resin. It is preferably a synthetic resin film layer which is excellent in heat resistance and electrical insulation, as well as being flexible and having high mechanical strength, and can be appropriately selected from known substrates.

[0061] The glass cloth should have a thickness of 10 μm or more and 50 μm or less and a weight of 45 g / m 2 More preferably, the thickness is 20 μm or more and 40 μm or less, and the weight is 30 g / m 2 The following is preferable. Since the thermal conductivity of glass cloth is relatively low, the thinner the glass cloth is, the better in terms of thermal conduction. However, if the glass cloth is too thin, the strength decreases and the desired reinforcing effect cannot be obtained. Or, the moldability becomes poor, so the thickness is preferably in the above-mentioned range. The glass cloth may be pre-filled with a silicone composition that forms a thermally conductive adhesive layer. Alternatively, the thermally conductive adhesive layer may be attached without pre-filling. In the latter case, it is preferable because the holes of the cloth are easily filled with the thermally conductive adhesive layer by performing thermocompression bonding.

[0062] The synthetic resin film layer usually has a thickness of 2 to 30 μm, preferably in the range of 5 to 20 μm. If the synthetic resin film layer is too thick, the thermal conductivity of the composite sheet of the present invention will be impaired. If it is too thin, the strength required for the reinforcing layer will be insufficient, and the withstand voltage characteristics will deteriorate, resulting in insufficient electrical insulation performance. Furthermore, the synthetic resin film layer is preferably a film layer without holes that would reduce the withstand voltage characteristics.

[0063] Examples of the synthetic resin include aromatic polyimide resin, polyamide resin, polyamideimide resin, polyester resin such as polyethylene naphthalate, and fluororesin such as polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkylvinylether copolymer, etc. When using the synthetic resin as the fluororesin, it is preferable to perform a chemical etching treatment on the surface of the film to be used using a metallic sodium / naphthalene-based treatment liquid from the viewpoint of improving adhesion.

[0064] In order to prevent a decrease in mechanical strength due to thermal deformation, the synthetic resin film is particularly preferably a heat-resistant film having a melting point of 200° C. or higher, preferably 250° C. or higher. An example of a synthetic resin film having heat resistance of a melting point of 250° C. or higher is Kapton (registered trademark) MT (product name, manufactured by Toray DuPont Co., Ltd.), which is an aromatic polyimide-based film.

[0065] [Method for producing thermally conductive composite] Next, a method for producing a thermally conductive composite using the thermally conductive adhesive layer according to the present invention and the reinforcing layer will be described in detail. The method for producing a thermally conductive composite of the present invention is to laminate the above-mentioned thermally conductive adhesive layers as outer layers on both sides of a reinforcing layer by room temperature compression or hot compression. The lamination method is not particularly limited, and may be appropriately performed according to a conventionally known method for producing a composite.

[0066] In the case of room temperature pressure bonding, for example, the thermally conductive adhesive layer formed in advance on the separator film may be transferred to both sides of the reinforcing layer. In the case of thermocompression bonding, the press tool is heated to 70 to 110°C and pressure-transferred in the same manner. Pressure bonding may be performed by press pressure bonding or roll pressure bonding. In addition, the composition of the thermally conductive adhesive layer may be diluted with a solvent and applied to both sides of the reinforcing layer, followed by drying to produce a thermally conductive composite.

[0067] When glass cloth is used as the reinforcing layer, the glass cloth may be sealed in advance with the above-mentioned heat-conductive silicone adhesive composition. When applying the heat-conductive silicone adhesive composition to the glass cloth, it is continuously applied to the glass cloth using a coating device such as a comma coater, knife coater, or kiss coater equipped with a drying furnace, a heating furnace, and a winding device, and the solvent is then dried and evaporated, followed by heating and curing at 130 to 170°C, preferably about 140 to 160°C, for about 20 to 40 minutes to obtain glass cloth sealed with the silicone composition.

[0068] Alternatively, a non-sealed glass cloth may be used, and the thermally conductive adhesive layer formed on the separator film may be transferred to laminate the thermally conductive adhesive layer and simultaneously perform the sealing process. In this case, it is preferable to heat the press tool to 70 to 110°C and transfer the layer. Press bonding may be performed using roll bonding or the like in addition to press bonding. If the transfer temperature is lower than 70°C, the thermally conductive adhesive layer may not adhere well to the glass cloth, and the mesh of the cloth may not be filled, which may result in a decrease in insulation and thermal conductivity. If the transfer temperature exceeds 110°C, there is a risk that the curing of the thermally conductive adhesive layer may proceed. The thickness of the entire thermally conductive composite is preferably 100 to 450 μm, and preferably 150 to 400 μm. In any of the above manufacturing methods, the separator film attached to the thermally conductive composite may be peeled off immediately after the thermally conductive adhesive layer is transferred to the reinforcing layer. Alternatively, the separator film may be left attached until immediately before use for the purpose of protecting the surface of the thermally conductive composite. In cases where a cutting process into a desired shape is performed after the manufacturing process of the thermally conductive composite, it is preferable to leave the separator film attached.

[0069] The above-mentioned thermally conductive composite also provides good adhesion between components by applying heat treatment during heating by a heat generating element or during mounting. By interposing it between a cooling component and a heat generating electronic component or a heat dissipating component, the two can be firmly fixed together. EXAMPLES

[0070] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The components (a) to (f) constituting the thermally conductive adhesive layer used in the following Examples and Comparative Examples are as follows. (a) Ingredients: (a-1) Dimethylpolysiloxane raw rubber having an average degree of polymerization of 6,000 (a-2) Dimethylpolysiloxane oil having an average degree of polymerization of 450 and vinyl groups at both ends (b) Ingredients: (b-1) Granular alumina having a volume average particle size of 1 μm (b-2) Granular aluminum nitride having a volume average particle size of 1 μm (b-3) Spherical alumina with a volume average particle size of 10 μm (b-4) Granular aluminum nitride having a volume average particle size of 20 μm (b-5) Spherical alumina having a volume average particle size of 45 μm (c) Ingredients: (c-1) Component A toluene solution (50% by mass, kinetic viscosity 10 mm) of a silicone resin in which 0.08 mol / 100 g of alkenyl groups are bonded only to D units and the ratio of M units to Q units is 0.9 2 / s) [ka] Expressed by the above average formula, R 1 is a methyl group, and R 2 is a vinyl group, a1 is 1.8, b1 is 1, c1 is 1, d1 is 1, e1 is 1, and a1 / (d1+e1)=0.9. (c-2) Component A toluene solution (60% by mass, kinetic viscosity 8 mm) of silicone resin with M / Q (molar ratio) = 1.2 and all the substituents bonded to the silicon atoms of the M units being methyl groups. 2 / s) [ka] Expressed by the above average formula, R 1are all methyl groups, a2 is 1.2, c2 is 0, d2 is 0, e2 is 1, and a2 / e2=1.2. Component (d): a cyclic organohydrogenpolysiloxane represented by the following formula: [ka] (e) Component: 2,5-dimethyl-2,5-di(t-butylperoxy)hexane Component (f): (f-2) Dimethylpolysiloxane having an average degree of polymerization of 30 and a trimethoxysilyl group at one end

[0071] The above components (a), (b), (c), and (f) were charged into a Shinagawa universal mixer in the amounts shown in Tables 1 and 3 below and mixed for 60 minutes. Next, components (d) and (e) were added in the amounts shown in Tables 1 and 3 below and mixed uniformly to obtain a uniform thermally conductive silicone adhesive composition.

[0072] [Forming the thermally conductive adhesive layer] An appropriate amount of toluene was added to the thermally conductive silicone adhesive composition obtained above. The toluene solution was applied onto a fluorine-treated PET film (separator film), and the toluene was volatilized at 80°C to form a thermally conductive adhesive layer having a thickness of 150 μm. Then, a separator film was further bonded to the exposed surface of the thermally conductive adhesive layer to obtain a thermally conductive adhesive layer protected on both sides by a separator film. The thickness of 150 μm is the thickness of only the thermally conductive adhesive layer, and does not include the thickness of the separator film. The release agent used for the surface treatment of the fluorine-treated PET film (separator film) is X-41-3035 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0073] [Molding of thermally conductive composites] A reinforcing layer was laminated to the separator film and the thermally conductive adhesive layer obtained by the above method by the following method to form a thermally conductive composite.

[0074] Two sheets of thermally conductive adhesive layers protected by separator films on both sides were prepared. The above-mentioned thermally conductive adhesive layers, which had been exposed by peeling off the separator film on one side, were then thermocompressed to both sides of a glass cloth (50 μm) at 90° C. to obtain a thermally conductive composite having a glass cloth as a reinforcing layer.

[0075] Two sheets of thermally conductive adhesive layers protected by separator films on both sides were prepared. The above-mentioned thermally conductive adhesive layers, which had been exposed by peeling off the separator film on one side, were then thermocompressed at 90°C onto both sides of a polyimide (10 μm) sheet to obtain a thermally conductive composite having a polyimide reinforcing layer.

[0076] In Examples 1 to 6 and Comparative Examples 1 to 6, the following evaluations were performed on the thermally conductive adhesive layer not having the reinforcing layer (thermally conductive adhesive layer having separator films on both sides of the adhesive composition layer). In Examples 7 and 9 and Comparative Examples 7 and 9, the following evaluations were performed on the composites having a glass cloth reinforcing layer. In Example 8 and Comparative Example 8, the following evaluations were performed on the composites having a polyimide reinforcing layer. The thicknesses of the thermally conductive adhesive layer and the entire thermally conductive composite are as shown in Tables 2 and 4. The size of the tape was 200 × 300 mm.

[0077] [Evaluation method] (1) Handling: When the thermally conductive adhesive layer or the adhesive layer surface of the thermally conductive composite was attached to a heat dissipation member (aluminum heat sink), it was evaluated whether the desired adhesion could be obtained. The separator film on one side was peeled off, the adhesive layer surface was attached to an aluminum heat sink, and then when the separator film on the other side was peeled off, the adhesive layer or composite was evaluated as to whether it was fixed without slipping from the heat sink. Those that were fixed without slipping were marked with an O, and those that were displaced were marked with an X, and these are shown in the table.

[0078] (2) Thermal conductivity: The thermally conductive adhesive layer or the thermally conductive composite was sandwiched between aluminum plates after removing the separator films on both sides, and was then uniformly pressed and cured at 150°C / 1hr using a dryer. The thermal resistance was measured using the laser flash method. The thermal conductivity was calculated from the relationship between thickness and thermal resistance.

[0079] (3) Shear adhesive strength to aluminum: The thermally conductive adhesive layer or thermally conductive composite with the thickness shown in the table, from which the separator films on both sides had been peeled off, was sandwiched between 10 x 10 mm square aluminum plates, uniformly pressed, and then heated and cured in a dryer at 150°C / 1 hr. The peel shear stress of the obtained test pieces was measured at room temperature using a Nordson 4000Plus bond tester.

[0080] (4) Dielectric breakdown voltage: Based on JIS K6249:2003, the dielectric breakdown voltage of the thermally conductive adhesive layer or the thermally conductive composite was measured after the separator films on both sides were peeled off.

[0081] (5) Tensile strength: After peeling off the separator films on both sides, the tensile strength of the thermally conductive adhesive layer or the thermally conductive composite was measured using an autograph according to JIS K6249:2003.

[0082] [Table 1]

[0083] [Table 2]

[0084] [Table 3]

[0085] [Table 4]

[0086] As shown in Tables 3 and 4, Comparative Example 1 is a silicone composition that does not contain the component (c-1), and after heat curing without pressure, the adhesive strength of the thermally conductive adhesive layer was significantly reduced. Comparative Example 2 is a silicone composition in which the blending amount of (b) the thermally conductive filler exceeds 7,500 parts by mass, and the obtained thermally conductive adhesive layer was brittle and difficult to handle. Comparative Example 3 is a silicone composition in which the blending amount of (c) the silicone resin is less than 150 parts by mass, and the obtained thermally conductive adhesive layer lacked cohesive force and was difficult to handle. Comparative Example 4 is a silicone composition in which the blending amount of (c) the silicone resin exceeds 600 parts by mass, and the obtained thermally conductive adhesive layer was brittle and difficult to handle. Comparative Example 5 is a silicone composition in which the blending amount of (d) the organohydrogenpolysiloxane exceeds 25 parts by mass, and the adhesive strength of the thermally conductive adhesive layer was reduced compared to Example 5. Comparative Example 6 is a silicone composition in which the blending amount of (e) the organic peroxide exceeds 50 parts by mass, and the adhesive strength of the thermally conductive adhesive layer was reduced compared to Example 6. In Comparative Example 7, a composite was formed from the thermally conductive adhesive layer of Comparative Example 1 and glass cloth, and in Comparative Example 8, a composite was formed from the thermally conductive adhesive layer of Comparative Example 1 and polyimide. Both composites showed a significant decrease in adhesive strength after heat curing. In Comparative Example 9, a silicone composition containing less than 1 part by mass of (d) organohydrogenpolysiloxane was used, and the resulting thermally conductive adhesive layer showed decreased wettability to the adherend and decreased adhesive strength.

[0087] In contrast, as shown in Tables 1 and 2, the thermally conductive adhesive layer formed from the thermally conductive silicone adhesive composition of the present invention in a thin film, and the thermally conductive composite having said adhesive layer, are easy to handle and can be easily mounted on an adherend, and have good thermal conductivity. Furthermore, the curing of the adhesive layer is accelerated even without the application of pressure during heat curing, and good adhesive strength can be achieved under simple curing conditions. [Industrial Applicability]

[0088] The thermally conductive silicone adhesive composition of the present invention is easy to handle and can be easily mounted on a heat dissipating member. In addition, it provides favorable thermal conductivity between a heat generating element and a heat dissipating member, and exhibits good adhesive strength, allowing for strong fixation between the members. Furthermore, when thermocompressing (bonding) the composition to a heat dissipating member, no high-pressure curing process is required, and the composition hardens by leaving it at high temperature for a certain period of time, providing sufficient adhesive strength, making it applicable to bonding a wide range of heat dissipating members.

Claims

1. A thermally conductive silicone adhesive composition comprising the following components (a) to (e): (a) Linear or branched organopolysiloxane: 100 parts by mass (b) Thermally conductive filler: 1,500 to 7,500 parts by mass (c) a three-dimensional network organopolysiloxane resin containing the following components (c-1) and (c-2): 150 to 600 parts by mass (c-1): the following general formula (1) 【Chemistry 1】 (In the formula, R 1 are each independently a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms; R 2 is an alkenyl group having 2 to 8 carbon atoms, and a1, b1, c1, d1, and e1 are numbers that satisfy 0<a1≦100, 0<b1≦100, 0≦c1≦100, 0≦d1≦100, and 0≦e1≦100, and are 0<d1+e1 and satisfy the range of 0.5≦a1 / (d1+e1)≦2. and the amount of alkenyl groups in the molecule is 0.05 to 0.15 mol / 100 g. (c-2): the following general formula (2) 【Chemistry 2】 (In the formula, R 1 are each independently a group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, and an aralkyl group having 7 to 10 carbon atoms, and a2, c2, d2, and e2 are numbers that satisfy 0<a2≦100, 0≦c2≦100, 0≦d2≦100, and 0<e2≦100, and also satisfy the range of 0.7≦a2 / e2≦2.

5. A three-dimensional network organopolysiloxane resin represented by (d) an organohydrogenpolysiloxane having two or more hydrosilyl groups per molecule: 1 to 25 parts by mass, and (e) Organic peroxide: 5 to 50 parts by mass.

2. 2. The thermally conductive silicone adhesive composition according to claim 1, wherein the proportion of component (c-1) relative to the total amount of component (c) is 10 to 60 mass %.

3. 3. The thermally conductive silicone adhesive composition according to claim 1, wherein the component (a) has an average degree of polymerization of 100 to 20,000.

4. 4. The thermally conductive silicone adhesive composition according to claim 1, wherein said component (a) contains two or more alkenyl groups in one molecule and has an average degree of polymerization of 100 to 20,000.

5. The thermally conductive silicone adhesive composition according to any one of claims 1 to 4, wherein component (b) is at least one member selected from the group consisting of metals, metal oxides, and metal nitrides.

6. The thermally conductive silicone adhesive composition according to any one of claims 1 to 5, wherein the silicone composition further comprises (f) 1 to 50 parts by mass of one or more selected from the following components (f-1) and (f-2): (f-1) An alkoxysilane compound represented by the following general formula (3): 【Chemistry 3】 (In the formula, R 3 are each independently an alkyl group having 6 to 15 carbon atoms; R 4 are each independently an alkyl group having 1 to 5 carbon atoms; R 5 are each independently an alkyl group having 1 to 6 carbon atoms, m is an integer of 1 to 3, and n is an integer of 0 to 2, with the proviso that m+n is an integer of 1 to 3. (f-2) Dimethylpolysiloxane represented by the following general formula (4): 【Chemistry 4】 (In the formula, R 5 are each independently an alkyl group having 1 to 6 carbon atoms, and p is an integer of 5 to 100.

7. A thermally conductive composite having a first thermally conductive adhesive layer laminated on one side of a reinforcing layer and a second thermally conductive adhesive layer laminated on the other side of the reinforcing layer, wherein the first and second thermally conductive adhesive layers are each independently made of the thermally conductive silicone adhesive composition according to any one of claims 1 to 6.

8. The thermally conductive composite according to claim 7 , wherein the thermally conductive adhesive layer has a thermal conductivity of 2.0 W / mK or more.

9. The thermally conductive composite according to any one of claims 7 to 8, wherein the reinforcing layer is made of a synthetic resin or a glass cloth.

10. The thermally conductive composite according to claim 9 , wherein the synthetic resin is at least one selected from the group consisting of aromatic polyimide resins, polyamide resins, polyamideimide resins, polyester resins, and fluororesins.

11. The thermally conductive composite according to any one of claims 7 to 10, further comprising a substrate surface-treated with a release agent, and at least one of the first thermally conductive adhesive layer and the second thermally conductive adhesive layer has a surface that does not contact the reinforcing layer and a release-treated surface of the substrate.

12. The thermally conductive composite according to claim 11 , wherein the release agent is a fluorine-modified silicone having a fluorine substituent bonded to the main chain.

Citation Information

Patent Citations

  • Heat dissipating pressure-sensitive adhesive composition and heat dissipating pressure-sensitive adhesive sheet using the same

    JP2002121529A

  • Silicone rubber composition, fixing roll and fixing belt

    JP2004233455A

  • Heat-conductive cured material and method for producing the same

    JP2008260798A

  • Silicone rubber composition and fixing roll

    JP2010202728A

  • Thermally conductive tacky-adhesive tape

    JP2014034652A